2016
DOI: 10.1039/c6ra23182a
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-folate coated mesoporous silica nanoparticles as a smart and pH-sensitive system for curcumin delivery

Abstract: Biocompatible pH and folate sensitive large pore MSNs with controllable and targeted CUR delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 73 publications
4
66
0
Order By: Relevance
“…As shown in XRD pattern (Figure 1(B)), the presence of CS on the surface of MSN could preserve a slight decrease in the intensity in comparison with MSN. The results are in accordance with published reports [29,31,33] and confirmed the formation of hexagonal structure of MSN.…”
Section: Xrd Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…As shown in XRD pattern (Figure 1(B)), the presence of CS on the surface of MSN could preserve a slight decrease in the intensity in comparison with MSN. The results are in accordance with published reports [29,31,33] and confirmed the formation of hexagonal structure of MSN.…”
Section: Xrd Analysissupporting
confidence: 93%
“…MSNs were prepared in the presence of mesitylene based on previous procedures [32,33]. Briefly, 7.0 ml of mesitylene, as a swelling agent of micelles, and 1.0 g of CTAB were added to a solution containing 480 ml of deionized water and 3.5 ml of NaOH (2 M).…”
Section: Preparation Of Msnmentioning
confidence: 99%
See 1 more Smart Citation
“…Haem compatibility of MSNs was adjudged by Haemolysis assay [22,23]. Triton X-100 treated RBCs were taken as a positive control with greatest lysis being observed and RBCs in PBS 7.4 were taken as negative control with unmistakably no lysis discovered.…”
Section: Haemolysis Studymentioning
confidence: 99%
“…However, another study of two differently-ordered pore structures, MCM-41 and MCM-48, showed that the cubic pore structure of the MCM-48 decreased the release rate, likely due to the longer mean free path of a drug molecule through the particle to reach the bulk solution Fickian diffusion and Case II transport, respectively [75]. However, the term fit values for MCM-41 and WO are smaller than the 0.43 lower bound, a result often seen in drug delivery studies using sub-100 nm particles [21,24,78]. In a study of particle size distribution on the kinetics of drug release [79], Ritger and Peppas found that variation in particle sizes resulted in accelerated drug release at early time points due to diffusion from particles smaller than the mean size and delayed release at later time points due to diffusion from particles larger than the mean size.…”
Section: Effect Of Pore Topologymentioning
confidence: 99%